From Weimar to Hitler Germany, 1918 - 33 - Feuchtwanger, E. J. 1924- (St. Martin's Press, 1993)
Weimar has become synonymous with catastrophic political failure, the prelude to the greatest moral and material disasters of the twentieth century. This book shows that such failure was never inevitable and that options remained tantalisingly open right up to Hitler's assumption of power. The democratic regime was saddled with heavy burdens stemming from defeat and never enjoyed general acceptance and legitimacy